(3QSGdI aj GdYed HGdQHY GdeLjHs
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO dI CeG HYO agPg QSGdI aj GdYed HGdQHY GdeLjH eTJedI Ydi ebOeI hYTQjf HGHG s
(3BNQgG (B:s
(3GdHGH GdYTQjf aj GdYeQ HGdchGcH s
(3Vef eLehY , JQJjHgG (B: 4s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs